Associations of combined physical activity and body mass index groups with colorectal cancer survival outcomes - Himbert, Caroline; Ose, Jennifer; Gigić, Biljana; Viskochil, Richard; Santuci, Kelly; Lin, Tengda; Ashworth, Anjelica; Cohan, Jessica N.; Scaife, Courtney L.; Jedrzkiewicz, Jolanta; Damerell, Victoria; Atkins, Katelyn M.; et al. (BMC cancer, 2023)
Physical activity and BMI have been individually associated with cancer survivorship but have not yet been studied in combinations in colorectal cancer patients. Here, we investigate individual and combined associations of physical activity and BMI groups with colorectal cancer survival outcomes.
Gesehen am 06.06.2023